The consideration and improvement of the sustainability performance monitoring framework for South African water boards - Thompson, Craig Howard (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
The South African Constitution ensures the right to adequate water, health services and a healthy environment (Government Gazette, 1996: 1251, 1255). Associated legislation and national strategies require that water resources and water services are rendered in a sustainable manner to ensure the rights enshrined in the Constitution are realised (Trialogue, 2010: 34; Government Gazette, 1998(c):11; Department of Water Affairs (DWA), 2003:9). South Africa is the 30th driest country in the world (DWA, 2013: iii), has impounded most of its surface water resources and has utilised 40 percent of the groundwater resource with remaining groundwater water quality uncertain (DWA, 2013:6-7). Despite achieving the basic water and sanitation Millennium Development Goals approximately 2.2 million and 4.5 million households still require access to basic services respectively (DWA, 2013:28-29). South Africa's ten water boards play a key role in bulk water service provision. They supply 57 percent of the countries domestic water supply (DWA, 2013:19) and are required to provide sustainable water services (Government Gazette, 1997:35). The Department of Water Affairs (Department of Water and Sanitation (DWS) as of June 2014) is mandated to monitor the performance of water boards and monitors of water boards through a Share Holders Compact (SHC) (Government Gazette, 1997: 50). The aim of the research is to achieve the following objectives: 1. Describe best practice for sustainability monitoring frameworks for water services. 2. Outline South Africa's water services mandatory and voluntary requirements with regards to sustainability monitoring. 3. Evaluate South Africa's current water services performance monitoring framework for water boards against findings from goals one and two. 4. Develop an improved framework for assessing South African water board's performance in their compliance and sustainability journey. 5. Demonstrate the improved framework functionality with a sample of water boards audited performance data from the 2012/13 financial year. A qualitative normative theory evaluation research method was utilised to achieve first three objectives of the research. The objectives to first understand current best practice for sustainability monitoring frameworks and the mandatory requirements for water services sustainability monitoring frameworks in South Africa was achieved via an extensive literature review. The evaluation research method was used where South Africa's current water services monitoring framework for water boards was evaluated for its adequacy to monitor sustainability compared with legislated requirements, national and international best practices (Hall et al, 2004: 55). Data collection for the evaluation research was sourced via documentation analysis. The 2012/13 water board audited annual reports, relevant national water services legislation, national and global water service sustainability monitoring best practices were critically reviewed. The review yielded a "thick description" of sustainability performance monitoring framework requirements that was used to evaluate the SHC (Holliday, 2002: 79). Despite the mandatory participation requirement for successful sustainability performance monitoring being met, the SHC was found to have inadequate aspects. It lacks an outcomes based approach, does not include environmental indicators, does not allow water board sustainability performance comparison and cannot indicate where individual water boards are on their sustainability journey. An improved sustainability performance monitoring framework for South African water boards is therefore proposed. This was developed with the assistance of an expert focus group drawn from multiple disciplines and organizations relevant to water board sustainability (Litosseliti, 2003: 8 and Hall et al, 2004: 51). The functionality of the framework is then demonstrated using 2012/13 audited performance data sourced from the annual reports of Overberg, Amatola, Rand and Umgeni Water boards. The proposed Water Services Sustainability Monitoring Framework (WSSMF) quantifies performance in terms of 10 water utility outcomes that are measured with 88 performance indicators that encompass the financial, social, environmental and governance dimensions of sustainability. The WSSMF demonstrated that the legislated intentions and best practice recommendations can be incorporated into an improved version of the SHC. Further refinement of the WSSMF is required. In depth engagement with DWS and all the water boards would promote the refinement of the indicator set, performance thresholds for indicators and indicator weighting. Further testing through a pilot project initiative would allow the WSSMF to be developed into a robust and adequate sustainability performance monitoring framework for South African water boards (Rametsteiner et al, 2011: 64; Muga and Mihelcic, 2008: 438; McAlphine and Birnie, 2005: 247 and van Leeuwen et al, 2012: 2192).
Keywords: South Africa -- Department of Water Affairs -- Management; Water-supply -- Law and legislation -- South Africa; Performance -- Management; Environmental auditing -- South Africa